Model characteristics of the kinematic structure of the left-foot side kick technique from a front stance by highly skilled athletes specializing in hand-to-hand combat - Vako , I.; Zhyrnov , O. (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. In any sport, it is crucial to have an effective and scientifically based model of athletes’ technical actions. The scientific and methodological literature offers several options for developing such a model. The first option: mathematical modelling (often with the help of computer facilities) of the standard model of the sport’s technique. The second one: the development of samples based on the analysis of the technique of motor actions of highly qualified athletes. Such standards, or models, are created based on the results of measurements of the biomechanical characteristics of the movement technique of a group of leading athletes. The data of such measurements are statistically processed, and as a result, we get average indicators of the characteristics of technical actions of leading athletes, which are called model characteristics and can be considered the most rational in any sport. The purpose of the study is to develop model characteristics of the kinematic structure of the technique of a side kick with the left foot from the front stance of highly skilled athletes specialising in hand-to-hand combat. Research methods: analysis of literature sources, video recording and biomechanical video computer analysis using the “Qualisys” optoelectronic system (which includes seven synchronised infrared cameras), methods of mathematical statistics. Results. When conducting a biomechanical analysis of the kinematic structure of the technique of performing a side kick with the left foot from the front stance, the first stage is to determine the phase-rhythm structure. The previously mentioned kick consists of 7 phases: preparation for the kick, encroachment, the double-support phase, kicking movement, contact, return of the kicking leg to the support, return to the fighting stance. The first 5 phases are the so-called active period of the kick, the purpose of which is to cause damage to the opponent. The last two phases are the passive period of the kick, the purpose of which is to return to the starting position to allow the next action to be taken. The total kick duration is 1,86 s. The duration of the active period is 0,85 s, i.e. 45,7% of the total kick duration, and the passive period is 1,01 s, i.e. 54,3%. The duration of the phase of preparation for a kick is 0,27 s, the task of this phase is to bring all biolinks of the athlete’s body into the most advantageous position for the performance of subsequent motor actions with minimal information for the opponent. The phase of encroachment lasts 0.19 s, its task is to put the feet on the ground into a comfortable position for the kick. In the double-support phase, the athlete must move the body weight to the supporting (“non-kicking”) leg, the duration of this phase is 0,12 s. The next phasethe kicking movement is aimed at moving the kicking biolink to the opponent (or sports equipment: punch, paw, etc.), its duration is 0,19 s. Conclusions. Indicators of the kinematic structure of the technique of performing a side kick with the left foot from the frontal stance when performed by highly skilled athletes specialising in hand-to-hand combat are determined. The obtained results can be used as model characteristics for less skilled athletes.